Competitive Interaction between Two Ant Species Facilitates Egg Hatching in Yellow-Spotted Amazon River Turtles (Podocnemis unifilis) - Baccaro, Fabricio Beggiato; Pereira, Francisco Raphael; Erickson, José (South American Journal of Herpetology, 2021)
Competition and facilitation are opposite sides of the species-interaction continuum. However, competitive interactions between species could result in facilitation for a third species. We evaluated the patterns of infestation and competitive exclusion between crazy-ants (Nylanderia sp.1) and fire-ants (Solenopsis geminata) and their effect on yellow-spotted Amazon River turtle (Podocnemis unifilis) nests in central Amazonia. We found that Nylanderia sp.1 colonizes P. unifilis nests at the start of their incubation period, whereas S. geminata was more abundant in nests during the final third of the incubation period. After colonization, the ant colonies remained in the nest through the breeding season. We did not observe differences in hatching success between nests with or without Nylanderia sp.1; however, in all nests colonized by S. geminata the entire P. unifilis clutch was lost. Our results suggest that during the incubation period, P. unifilis clutches benefit from Nylanderia sp.1 colonization, which prevents nest colonization by S. geminata. During the most defenseless stage in the life history of turtles, indirect facilitation by Nylanderia sp.1 appears to support the coexistence between prey, P. unifilis clutches, and their main predator, S. geminata, during the incubation period. ©
Keywords: Associative resource; Hatching success